On Fully Degenerate Daehee Numbers and Polynomials of the Second Kind - Sang Jo Yun; Jin-Woo Park (Journal of Mathematics, 2020)
In a study, Carlitz introduced the degenerate exponential function and applied that function to Bernoulli and Eulerian numbers and degenerate special functions have been studied by many researchers. In this paper, we define the fully degenerate Daehee polynomials of the second kind which are different from other degenerate Daehee polynomials and derive some new and interesting identities and properties of those polynomials.